Data from: Widespread introgression of mountain hare genes into Fennoscandian brown hare populations - Levänen, Riikka; Thulin, Carl-Gustaf; Spong, Göran; Pohjoismäki, Jaakko L.O.; Pohjoismäki, Jaakko L. O. (Data Archiving and Networked Services (DANS), 2019)
In Fennoscandia, mountain hare (Lepus timidus) and brown hare (Lepus europaeus) hybridize and produce fertile offspring, resulting in gene flow across the species barrier. Analyses of maternally inherited mitochondrial DNA (mtDNA) show that introgression occur frequently, but unavailability of appropriate nuclear DNA markers has made it difficult to evaluate the scale- and significance for the species. The extent of introgression has become important as the brown hare is continuously expanding its range northward, at the apparent expense of the mountain hare, raising concerns about possible competition. We report here, based on analysis of 6833 SNP markers, that the introgression is highly asymmetrical in the direction of gene flow from mountain hare to brown hare, and that the levels of nuclear gene introgression are independent of mtDNA introgression. While it is possible that brown hares obtain locally adapted alleles from the resident mountain hares, the lower levels of mountain hare alleles among allopatric brown hares suggest that hybridization is driven by stochastic processes. Interspecific geneflow with the brown hare is unlikely to have major impacts on mountain hare in Fennoscandia, but direct competition may. SNP genotypes for 6833 loci from 21 mountain hares (Lepus timidus) and 27 brown hares (Lepus europaeus)SNP genotypes for 6833 loci from 21 mountain hares (Lepus timidus) and 27 brown hares (Lepus europaeus) from Sweden and Finland. Data sheet includes sample number, sampling location coordinates, mtDNA haplotype and notes for species co-existence at the sampling location (sympatry/allopatry).SNPdataset_Levanen_Final.xlsx